Combining Satellite Tracking and Remote Sensing to Identify Activity Pattern and Habitat Selection of Coastal Shorebirds: A Case Study of Pied Avocets in Bohai Bay, China - Dong Li; Xiyong Hou; Kai Liu; Yingxu Gao; Yang Wu (Ecology and Evolution)
ABSTRACT In the context of intense interference from human activities and massive loss of natural wetlands in coastal zones, it is crucial to understand the behavioral ecology of shorebirds for formulating targeted conservation measures. Based on satellite tracking and remote sensing techniques, our research investigated the activity pattern and habitat selection characteristics of the Pied Avocet (Recurvirostra avosetta ) in Bohai Bay, China. The results showed that Pied Avocets are relatively flexible in habitat selection in Bohai Bay. There are obvious individual differences in their residence time (119–210 days) and activity range (core home range from 15.34 to 95.12 km2). Pied Avocets may only move around a fixed breeding site throughout the breeding season, or they may transfer to another location for a second breeding. The mariculture, salt pan, and industrial‐mining land are the main components of the Pied Avocets' habitat, and the proportion of their area in the main and core home ranges is > 10%. The species prefers sparsely vegetated areas near coastlines and water bodies as habitats and has a certain tolerance for human disturbance. Our findings could provide specific management advice for alleviating human‐bird conflicts in the highly developed coastal zones. The study on the activity pattern and habitat selection of the Pied Avocet offered technical and data support for shorebirds habitat protection.